Epidemiology of congenital heart disease in Brazil - Pinto Júnior,Valdester Cavalcante (2015)
AbstractIntroduction:Congenital heart disease is an abnormality in the structure or cardiocirculatory function, occurring from birth, even if diagnosed later. It can result in intrauterine death in childhood or in adulthood. Accounted for 6% of infant deaths in Brazil in 2007.Objective:To estimate underreporting in the prevalence of congenital heart disease in Brazil and its subtypes.Methods:The calculations of prevalence were performed by applying coefficients, giving them function rates for calculations of health problems. The study makes an approach between the literature and the governmental registries. It was adopted an estimate of 9: 1000 births and prevalence rates for subtypes applied to births of 2010. Estimates of births with congenital heart disease were compared with the reports to the Ministry of Health and were studied by descriptive methods with the use of rates and coefficients represented in tables.Results:The incidence in Brazil is 25,757 new cases/year, distributed in: North 2,758; Northeast 7,570; Southeast 10,112; South 3,329; and Midwest 1,987. In 2010, were reported to System of Live Birth Information of Ministry of Health 1,377 cases of babies with congenital heart disease, representing 5.3% of the estimated for Brazil. In the same period, the most common subtypes were: ventricular septal defect (7,498); atrial septal defect (4,693); persistent ductus arteriosus (2,490); pulmonary stenosis (1,431); tetralogy of Fallot (973); coarctation of the aorta (973); transposition of the great arteries (887); and aortic stenosis 630. The prevalence of congenital heart disease, for the year of 2009, was 675,495 children and adolescents and 552,092 adults.Conclusion:In Brazil, there is underreporting in the prevalence of congenital heart disease, signaling the need for adjustments in the methodology of registration.